Analysis of Human Resource Development in Optimizing the Use of the Goods in and Out Information System at the Office of the Regional Research and Innovation Agency of Central Sulawesi Province - Haris Abdul Kadir; Farid; Dicky Yusuf; Awaluddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research aims to analyse human resource development (HRD) in optimising the use of the Goods In and Out Information System (SIKMB) at the Office of the Regional Research and Innovation Agency of Central Sulawesi Province. This study employed a qualitative approach, utilizing interview methods with five informants who are employees at the institution. The results indicate that human resource development at the Regional Research and Innovation Agency of Central Sulawesi continues to face several key challenges, including a lack of in-depth understanding of standard operating procedures (SOPs) and limited technical training on the use of the information system. Although the SIKMB system has been implemented, many employees have not been able to maximise the use of the system's features. Additionally, issues related to outdated technological infrastructure and a lack of coordination between units pose obstacles to efficient goods management. Therefore, this study recommends the need for ongoing training, updating technological infrastructure, improved inter-departmental coordination, and the implementation of motivation and incentive policies to enhance staff performance in using the system. The results of this study are expected to contribute to human resource development and increased operational efficiency at the Office of the Regional Research and Innovation Agency of Central Sulawesi